Non-Coding RNA m6A Modification in Cancer: Mechanisms and Therapeutic Targets - Chen, Da-Hong; Zhang, Ji-Gang; Wu, Chuan-Xing; Li, Qin (Frontiers in Cell and Developmental Biology, 2021)
Recently, N6-methyl-adenosine (m6A) ribonucleic acid (RNA) modification, a critical and common internal RNA modification in higher eukaryotes, has generated considerable research interests. Extensive studies have revealed that non-coding RNA m6A modifications (e.g. microRNAs, long non-coding RNAs, and circular RNAs) are associated with tumorigenesis, metastasis, and other tumour characteristics; in addition, they are crucial molecular regulators of cancer progression. In this review, we discuss the relationship between non-coding RNA m6A modification and cancer progression from the perspective of various cancers. In particular, we focus on important mechanisms in tumour progression such as proliferation, apoptosis, invasion and metastasis, tumour angiogenesis. In addition, we introduce clinical applications to illustrate more vividly that non-coding RNA m6A modification has broad research prospects. With this review, we aim to provide novel insights into non-coding RNA m6A modification in cancer progression and targeted therapy, facilitating further research.